Proposta de planejamento estratégico para a empresa RB Papelaria - Bigolin, Renan (2017)
With the globalization of markets, the current economic crisis and the strong market competition generated by the mass diffusion of e-commerce, it became necessary for companies to prepare themselves to overcome Environmental contingencies and to monitor the new market trends to survive and thrive. In this way, organizations need to find ways to prevent future problems making predictions that provide an achievable level of security in making decisions. For this reason, the present work proposes to use an excellent management tool, called strategic planning, to diagnose the current situation at RB Stationery Store and create objectives and strategies that ensure the continuity of this family business. In the research methodology was developed a case of study, that include interviews applied to the owner and the clients, and the researcher observation, to be possible to collect data, perceptions, and opinions, with the interest of the clients to know the internal and external environment of the organization. Based on the model proposed by Vasconcellos Filho and Pagnoncelli (2001), and through the collected data, the Strategic Planning stages were created. Was defined to RB Stationery Store: the business, mission, principles, and vision, as well as the main objective, strategies and action plans in a structured way to achieve the set goal. With the application of this Plan, RB Stationery Store is now focused on expanding its client portfolio, becoming more competitive, and therefore structured to survive longer.